Long term follow-up in two siblings with Sengers syndrome: Case report - Chiara Panicucci; Maria Cristina Schiaffino; Claudia Nesti; Maria Derchi; Gianluca Trocchio; Mariasavina Severino; Nicola Stagnaro; Enrico Priolo; Federico Zara; Filippo M. Santorelli; Claudio Bruno (BMC, 2022)
Abstract Background Sengers syndrome is characterized by congenital cataract, hypertrophic cardiomyopathy, mitochondrial myopathy, and lactic acidosis associated with mutations in AGK gene. Clinical course ranges from a severe fatal neonatal form, to a more benign form allowing survival into adulthood, to an isolated form of congenital cataract. Thus far few reported cases have survived the second decade at their latest examination, and no natural history data are available for the disease. Case presentation Here we provide a 20-year follow-up in two siblings with a benign form of Sengers syndrome, expanding the phenotypical spectrum of the disease by reporting a condition of ovarian agenesis. Conclusion To our knowledge, this report provides the first longitudinal data of Sengers syndrome patients.